P-062 The Impact of Affective Spectrum Disorders on Health Care Resource Utilization in Patients with Inflammatory Bowel Disease. (February 2017) - Gorrepati, Venkata Subhash; Navabi, Seyedehsan; Stuart, August; Tinsley, Andrew; Williams, Emmanuelle; Coates, Matthew
Abstract : Background: Previous studies have demonstrated that individuals with inflammatory bowel disease and affective spectrum disorders (ASD) utilize a significant amount of health care resources, particularly when compared to many other chronic gastrointestinal and psychiatric conditions respectively. Given the frequent co-incidence of these disorders, we undertook this study to evaluate patterns of health care resource utilization in IBD patients with ASD. Methods: We performed a retrospective analysis using a consented IBD natural history registry between January 1, 2015 and June 30, 2016 from a single tertiary care referral hospital system with a dedicated IBD center. Presence of anxiety or depression was determined based upon responses to the Hospital Anxiety and Depression Scale (HADS) (sub-score = 8 or greater indicating clinical significance for each). We also abstracted data regarding demographic variables (including age and gender), IBD severity, extent and subtype (Ulcerative Colitis [UC] and Crohn's Disease [CD]), medication use (including antipsychotics, anxiolytics, antidepressants, opiates, biologics, immunomodulators, mesalamines, and corticosteroids) and health care utilization (including number of imaging studies, clinic visits, ED visits, hospitalizations, total hospital days, surgeries and clinic "no shows" [i.e., missed clinic appointments]). Results: Two hundred sixty-two total IBD patients (130f:132 m) were included in this study. Eighty-six had UC (32.8%; 40f:46 m), 163 had CD (62.2%, 83f:80 m) and 13 had indeterminate colitis (5.0%, 7f:6 m). One hundred twenty-one IBD patients (46.1%) were found to have clinically significant anxiety and/or depression scores. IBD patients with ASD were more likely to undergo imaging studies (57.3% versus 42.7%, P < 0.05), visit the ED (66.1% versus 23.6%, P < 0.0001), receive corticosteroids (57.7% versus 37.9%, P < 0.05), receive opiates (30.8% versus 14.6%, P < 0.01) and/or have at least one "no show" (40.2% versus 20.1%, P < 0.01). They also had more imaging studies (1.55 versus 0.80, P < 0.01), visits to the ED (1.2 versus 0.5, P < 0.05), and/or "no shows (0.84 versus 0.40, P = 0.01). IBD patients with ASD also trended toward having a larger number of surgeries during the study period (0.34 versus 0.20, P = 0.06). Biologic therapy was more common in this population (69.5% versus 51.4%, P < 0.01) while mesalamine and immunomodulator use were not. When patients were divided into IBD subtype, only CD patients with ASD demonstrated any significant difference in resource use during the study period (with the likelihood of a "no-show" = 47.6% versus 22.8% [ P < 0.01], corticosteroid prescription = 57.7% versus 38.0% [ P < 0.05], and opiate prescription = 34.1% versus 16.5% [ P < 0.05]). Conclusions: IBD patients with anxiety and depression demonstrate significantly increased levels of health care resource utilization, including use of diagnostic and therapeutic interventions. They are also significantly more likely to utilize medications that have potentially deleterious long-term consequences, such as opiates and corticosteroids. Finally, they are much more likely to miss clinic visits, making disease management more difficult and resulting in misuse of a valuable, finite resource. This study confirms the findings of previous investigations that have demonstrated a relationship between IBD, ASD and resource utilization and suggests that CD patients in particular are at increased risk for these issues. In order to minimize exposure to potentially harmful therapies and to avoid misuse of valuable resources, it is critical to incorporate strategies that identify ASD and manage its consequences in IBD patients.